(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Hypertension, or high blood pressure, is a major cause of mortality among individuals who are obese in developed nations. This medical condition is often referred to as a silent killer, as it can affect millions of people worldwide and elevate the death rate. Hypertension can lead to severe health complications without obvious symptoms and is linked to low levels of physical activity and excessive caloric intake. If left unaddressed, it can cause serious health issues such as cardiovascular diseases and stroke.